The Effects of Inflation, Interest Rates, and Exchange Rates on the Stock Returns of Companies Listed in the IDX30 Index of the Indonesia Stock Exchange during 2021–2025 - Tiana Bela; Muhammad Suparmoko; Ende (Jurnal Investasi Islam, 2026)
This study aims to analyze the effect of inflation, interest rates, and exchange rates on stock returns in companies listed on the IDX30 index on the Indonesia Stock Exchange during the 2021–2025 period. This study uses a quantitative approach with secondary data obtained from the Indonesia Stock Exchange, Bank Indonesia, and the Central Bureau of Statistics. The research sample consists of 19 companies consistently listed on the IDX30 index during the observation period, with a total of 95 observations. The analytical method used is panel data regression analysis with the help of Eviews 12 software, and the model used in this study is the Common Effect Model (CEM). The results show that inflation has a positive and significant effect on stock returns, interest rates have a negative and significant effect on stock returns, while the exchange rate has no significant effect on stock returns. Simultaneously, inflation, interest rates, and the exchange rate have a significant effect on stock returns. The coefficient of determination shows that the independent variables are able to explain 18.38% of stock returns, while the remainder is influenced by other factors outside the research model. The results of this study provide implications that macroeconomic factors are still an important consideration in making investment decisions on leading stocks included in the IDX30 Index.